2011
DOI: 10.1158/0008-5472.can-10-4417
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Proline-Rich Region of the Murine Metastasis Susceptibility Gene Brd4 Promotes Epithelial-to-Mesenchymal Transition- and Stem Cell-Like Conversion

Abstract: The bromodomain-containing chromatin-modifying factor BRD4 is an inherited susceptibility gene for breast cancer progression and metastasis, but its functionality in these settings has yet to be explored. Here we show that deletion of either of the BRD4 bromodomains had modest effects on the metastatic suppression ability of BRD4. In contrast, expression of the natural short isoform of BRD4 that truncates the protein after the SEED domain restored progression and metastatic capacity. Unexpectedly, deletion of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 35 publications
11
92
0
Order By: Relevance
“…The inherited differences in immune components in the mouse that predict DMFS in ER − patients is, to the best of our knowledge, unique evidence that polymorphisms in stromal tissue play an important role in predisposing women to disseminated disease. Our previous efforts to identify metastasis susceptibility genes have focused on tumor-autonomous factors (25,(33)(34)(35) rather than nonautonomous factors, such as immune response. Interestingly, epidemiology studies have demonstrated that polymorphisms in the human orthologs of these cell-autonomous metastasis susceptibility genes are prognostic only in ER + patients (36), consistent with the finding that the cell-autonomous TPX2 mitotic spindle checkpoint network is significant only in ER + patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inherited differences in immune components in the mouse that predict DMFS in ER − patients is, to the best of our knowledge, unique evidence that polymorphisms in stromal tissue play an important role in predisposing women to disseminated disease. Our previous efforts to identify metastasis susceptibility genes have focused on tumor-autonomous factors (25,(33)(34)(35) rather than nonautonomous factors, such as immune response. Interestingly, epidemiology studies have demonstrated that polymorphisms in the human orthologs of these cell-autonomous metastasis susceptibility genes are prognostic only in ER + patients (36), consistent with the finding that the cell-autonomous TPX2 mitotic spindle checkpoint network is significant only in ER + patients.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, transcriptional analysis of the metastasis susceptibility gene Bromodomain 4 (Brd4) (19) was performed. Brd4 is transcribed as two isoforms, the longer of which is antimetastatic (19) and induces a gene signature associated with longer DMFS, but the short isoform is prometastatic and induces a gene signature indicative of poorer DMFS (20). The expression of the TPX2 network was therefore examined in the highly metastatic Mvt1 mouse mammary tumor cell line (17) stably expressing either the long or short Brd4 isoforms.…”
Section: Transcriptional Network Significantly Overlap Between Diffementioning
confidence: 99%
See 2 more Smart Citations
“…To date only a few groups have addressed this issue. A number of molecular mechanisms which potentially underlie this stem cell/EMT plasticity have been identified including the p130Cas/Cyclooxygenase-2 axis and Brd4 [38,39]. Meyer et al [19] have also demonstrated that single non-invasive epitheliallike CD44 -cells [19].…”
Section: Plasticity Of Breast Cancer Stem-like Cells Plasticity Betwementioning
confidence: 99%